Ghost in the Cartridge Nostalgia and the Construction of the JRPG Genre - Mallindine, Jayme Dale (2016)
This paper reveals an affective and nostalgic foundational component of the Japanese Role-Playing-Game (JRPG) video game genre through an investigation of its history and use as seen on gaming blogs, forums, and videos. As a result of new technology, like the Microsoft Xbox Console, hitting the market in the early 2000s, the term JRPG started becoming popular as consoles and computers gained the capacity to play games that were previously exclusive to either one or the other. Prior to that, the dominant producer of video game consoles was Japan. As Western-made RPGs, which were generally made for computers, became increasingly more available for console play as a result of console-computer convergence, the term JRPG became a way for gamers to distinguish games that felt similar to RPGs made for Japan-made consoles in the 80s and 90s. Now the Japan aspect of the genre's name is a way of negotiating identity and memory in a rapidly changing technological landscape, rather than being used specifically to identify a game's country of origin. This genre, which runs counter to typical genre organizational schemes based on either game-play mechanics or narrative themes, further illuminates how memory and nostalgia can affect how players categorize their gaming worlds.
Keywords: JRPGs; Japan; Japanese Role-Playing games; RPGs; Role-Playing Games; Computer Games; console games; Fan Studies; Genre; History; Memory; Nostalgia; Video Games